Functional differences between protamine preparations for the transfection of mRNA. (1st January 2020) - Jarzebska, Natalia Teresa; Lauchli, Severin; Iselin, Christoph; French, Lars E; Johansen, Pal; Guenova, Emmanuella; Kündig, Thomas M; Pascolo, Steve
Abstract: Protamine is a natural cationic peptide mixture used as a drug for the neutralization of heparin and in formulations of slow-release insulin. In addition, Protamine can be used for the stabilization and delivery of nucleic acids (antisense, small interfering RNA (siRNA), immunostimulatory nucleic acids, plasmid DNA, or messenger RNA) and is therefore included in several compositions that are in clinical development. Notably, when mixed with RNA, protamine spontaneously generates particles in the size range of 20–1000 nm depending on the formulation conditions (concentration of the reagents, ratio, and presence of salts). These particles are being used for vaccination and immuno-stimulation. Several grades of protamine are available, and we compared them in the context of complex formation with messenger RNA (mRNA). We found that the different available protamine preparations largely vary in their composition and capacity to transfect mRNA. Our data point to the source of protamine as an important parameter for the production of therapeutic protamine-based complexes.